Pengaruh Minyak Zaitun Untuk Mengurangi Striae Gravidarum Pada Ibu Hamil - Putri Elza Fernanda; Enny Yuliaswati (Lembaga Pengembangan Kinerja Dosen, 2023)
Background; During pregnancy, the mother's body undergoes hormonal changes that affect the entire organ system. One of the common issues that arise is striae gravidarum, or stretch marks on the skin. Olive oil contains beneficial components for addressing striae gravidarum. An initial survey conducted at PMB Wulan Mardikaningtyas in Kartasura indicated that more than 20 pregnant mothers experience striae gravidarum. The objectives of the research; To investigate the effect of olive oil in reducing striae gravidarum in pregnant mothers. Method; This study utilized a one-group experimental design method. Univariate data analysis was employed to examine frequency distribution, while bivariate analysis was used to assess the impact of olive oil intervention on striae gravidarum. Results; Prior to intervention, the severity level of striae gravidarum was classified as moderate in 9 pregnant mothers (45%) and severe in 7 pregnant mothers (35%). Following the intervention, a majority of respondents exhibited reduced severity levels of striae gravidarum, with 9 pregnant mothers (45%) in the moderate category and 7 pregnant mothers (35%) in the mild category. A difference was observed in the striae gravidarum scale before and after the olive oil intervention. Summary: There is a difference in the striae gravidarum scale before and after the olive oil intervention among pregnant mothers.